Green Security Plugin for Pervasive Computing using the HADAS toolkit - Muñoz-Guerra, Daniel Jesús; Montenegro-Montes, José Antonio; Pinto-Alarcón, Mónica; Fuentes-Fernández, Lidia (IEEE, 2017)
Energy is a critical resource in pervasive computing devices. However, information about energy consumption is not directly accessible through software development environments, making it difficult to reuse the knowledge provided by existing energy-consumption experimental studies. To address this limitation, this paper presents a solution to enrich Android Studio with energy consumption information. We have developed a Green Security Plugin that provides energy-aware information to developers that make use of Android Security API. This plugin has been developed taking advantage of the functionalities provided by the HADAS toolkit. HADAS is a repository of energy consuming concerns in which researchers can store the energy measures obtained during their experimental studies and developers can perform a sustainability analysis to make green design/implementation decisions.
Keywords: Criptografía (Informática); Software sustainability; Cryptographic algoritms; Software energy awareness